Improved PECVD SixNy film as a mask layer for deep wet etching of the silicon. (6th September 2017) - Han, Jianqiang; Yin, Yi Jun; Han, Dong; Dong, LiZhen
Abstract: Although plasma enhanced chemical vapor deposition (PECVD) silicon nitride (Si x N y ) films have been extensively investigated by many researchers, requirements of film properties vary from device to device. For some applications utilizing Si x N y film as the mask Layer for deep wet etching of the silicon, it is very desirable to obtain a high quality film. In this study, Si x N y films were deposited on silicon substrates by PECVD technique from the mixtures of NH3 and 5% SiH4 diluted in Ar. The deposition temperature and RF power were fixed at 400 °C and 20 W, respectively. By adjusting the SiH4 /NH3 flow ratio, Si x N y films of different compositions were deposited on silicon wafers. The stoichiometry, residual stress, etch rate in 1:50 HF, BHF solution and 40% KOH solution of deposited Si x N y films were measured. The experimental results show that the optimum SiH4 /NH3 flow ratio at which deposited Si x N y films can perfectly protect the polysilicon resistors on the front side of wafers during KOH etching is between 1.63 and 2.24 under the given temperature and RF power. Polysilicon resistors protected by the Si x N y films can withstand 6 h 40% KOH double-side etching at 80 °C. At the range of SiH4 /NH3 flow ratios, the Si/N atom ratio of films ranges from 0.645 to 0.702, which slightly deviate the ideal stoichiometric ratio of LPCVD Si3 N4 film. In addition, the silicon nitride films with the best protection effect are not the films of minimum etch rate in KOH solution.